HSBC in East Asia (before the 2008 credit crunch) - Rowley, Chris, 1959- (SAGE knowledge. Cases., 2016)
We are given an example of how human resources management (HRM) is practiced within the increasingly important East Asian financial markets. We look at HSBC bank's training and developing programmes, as well as the company's recruitment practices within the cultural challenges of a globalized economy.